Uji Antioksidan Ekstrak Metanol Kulit Batang Pule (Alstonia scholaris) khas Kalimantan dengan Metode DPPH: Antioxidant Test of Methanol Extract of Pule Bark (Alstonia scholaris) typical of Kalimantan with the DPPH Method - Nur Halimah; Mahfuzun Bone; Fajar Prasetya (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Pule (Alstonia scholaris) is one of the plants that are empirically often used in medicine. Pule bark contains flavonoids which can generally be used as antioxidants. This study aims to determine the content of secondary metabolites and antioxidant activity of the methanol extract of pule bark by determining the IC50 value of the extract. The secondary metabolite test was carried out by reacting the extract with phenolic test reagents, steroids, terpenoids, saponins, flavonoids and alkaloids. The antioxidant activity test was carried out using the DPPH method (2,2-Diphenyl-1-Picrylhydrazil). Antioxidant activity was measured by the ability of the methanol extract of Pule bark to reduce DPPH which was measured using a UV-Vis Spectrophotometer so that absorbance data was obtained and then processed by linear regression method. The results showed that the extract contained phenolic and flavonoid compounds. While the DPPH test showed that the extract had weak antioxidant activity with an IC50 value of 472.473 ppm.